Feno de capim tifton, casca de soja e caroço de algodão como fonte de fibra em dietas à base de palma forrageira para ovinos - COSTA, Suellen Brandão de Miranda (2009)
The purpose of this paper was to evaluate the effect of different sources of fiber (tifton hay, soybean hulls and whole cottonseed) in forage cactus-based diets for sheep in feedlot termination. In the research, 21 sheep were used with no defined racial standard, non-castrated with initial average weight of 18.90 ± 1.07 kg. The intake of dry and organic matter, total carbohydrates and total digestive nutrients, were not influenced by the different fiber sources (1.10; 0.97; 0.73 and 0.80 kg/day, respectively). The animals which received diets containing whole cottonseed presented lower intake of crude protein and neutral detergent fiber (0.11 and 0.29 kg/day respectively) and greater intake of ether extract (0.048 kg/day). The different sources of fiber propitiated similar feeding time, however the rumination time was greater for tifton hay (429.05 min/day). The digestibility coefficient of dry and organic matter differed between the treatments, where the diet with soybean hulls showed greater digestion(83.23 and 86.72%, respectively). The diet with whole cottonseed presented the smallest digestibility coefficient of crude protein (68.95%) and greatest for ether extract (85.94%). The daily weight gain of animals fed with whole cottonseed was smallest (0.11 kg/day). It is recommended the use of tifton hay or soybean hulls as a source of fiber in forage cactus-based diets for SPRD sheep in feedlot termination.